Measurement of Thermal Conductivity along the Radial Direction in a Vertical Cylindrical Packed Bed. (3rd February 2015) - Bedarkar, Swaren; Viswanathan, Nurni Neelakantan; Ballal, Nidambur Bharatha
Abstract : Heat transfer in packed beds and their thermal response have been of great interest for scientists and engineers for the last several years, since they play a crucial role in determining design and operation of reactors. Heat transfer of a packed bed is characterised through lumped parameter, namely, effective thermal conductivity. In the present studies, experiments were performed to investigate the thermal conductivity of a packed bed in radial direction. The packed bed was formed using iron ore particles. To determine the effective thermal conductivity a new transient methodology is proposed. The results obtained were compared with the models proposed by ZBS and Kunii and Smith.